The Influence of Consumption Patterns, Dietary Restrictions and Socio-Economic Factors on Stunting Incidents - Dadi, Gingngu Rambu Kuba; Laga Nur, Marselinus; Riwu, Rut Rosina (Faculty of Public Health, Nusa Cendana University, 2021)
Stunting is a condition in which the length/height of a toddler is less when compared to age. Body length/height of toddlers is seen based on the z-score value less than minus two (-2 SD). Stunting is a chronic nutritional problem caused by various factors and is intergenerational. This study was conducted to know the effect of food consumption patterns, dietary restrictions, and family socio-economic factors on the incidence of stunting in children under five in the work area of the Mananga Health Center. This type of research is an analytical observational study with a case-control design. The population of this study is mothers who have children under five aged 24-59 months and a sample of 96 people. The data collected were analyzed using the Chi-Square test. The results of the bivariate analysis showed variables of food consumption patterns (p=0,000), dietary restrictions (p=0,001), and family socioeconomic factors (education p=0,000, occupation p=0,000, the number of family members p=0,000, and the income p=0,000) has an effect on the incidence of stunting in children under five in the work area of the Mananga Health Center. Therefore, it is recommended that mothers who have children under five can change their children’s food consumption patterns starting from the selection of food, the type of good food and the frequency of eating their children for early treatment, as well as the need for monitoring the growth of toddlers by measuring their height regularly through Posyandu in the area health center work.